Três ensaios em crescimento econômico regional - Silva, Caio Cezar Fernandes da (2022)
The present work is a set of three independent essays on regional economics. The first essay aims to provide a theoretical understanding of the phenomenon of growth and regional inequality from the cumulative causation approach. A growth model led by aggregate demand is presented with the operation of dynamic increasing returns, at first the kaldorian mechanism is presented in which economic growth is led by exports and from them a process of selfreinforcement is triggered, inducing endogenous increases in labor productivity, which, in turn, reduction in the level of prices that reinforce the region's commercial advantages. An alternative to understand cumulative causation is presented when we admit the existence of autonomous domestic expenditures also capable of triggering self-reinforcing processes through endogenous productivity growth, affecting the commercial advantages of the region. This alternative substantially changes the understanding of the phenomenon of regional economic growth and the possibility of other avenues for effective growth policies. Finally, we discuss the importance of differentials in the ability to induce technical progress through regions as a limiting factor in the expansionist functioning of cumulative causation historically. The second essay aims to verify the differences in the capacity of the Brazilian states' economies to generate employment against their aggregate product growth performance. The period analyzed are the year’s corresponding to the ascending part of the economic cycle between 2002-2014, the subsequent period of crisis and near stagnation between 2014 and 2019 is also analyzed. Employment elasticities of economic growth were estimated from regressions using panel data, the employment data used are from the National Household Sample Survey (PNAD) and for the product level, data compiled by the Applied Economic Research Institute (IPEA) were used. The results show that the states of the North Region of the country, with few exceptions, tend to have greater capacity to incorporate employment into their economies, while economies in other regions grew in a regime that prioritized the advancement of labor productivity. During the period of crisis these relationships changed significantly without a dominant pattern between regions. It was shown that despite having greater capacity to generate employment from growth, this dynamic observed between 2002 and 2014, interrupted by the crisis, was not able to create trends towards reducing unemployment in the North and Northeast states, as observed in the states of the other regions. of the country, indicating that even if they can recover the level of output, they obtained in 2014, it will not be enough to start reducing the level of unemployment. The third essay analyzes the economic growth of Brazilian states between 2002 and 2019, demonstrating that even during the ascending part of the economic cycle there were important differences between the growth trajectories of the states. A growth model is presented that shows the fundamentals of divergence between regions from an aggregate demand approach. Finally, we present evidence from Moran's differential statistics in which spatial growth patterns are transformed according to the economic cycle.